Islamic Worldview and Humanism: A Short Response - Martin Putra Perdana Martin; Muhammad Wahyudi (Indonesian Journal of Islamization Studies, 2024)
Humanism is a contemporary thought that is being imported by liberal thinkers into the Islamic world. This Western-originated notion is not without its problems; in fact, it comes with many problems. The main problem lies in how they conceptualise the relationship between God, humans and nature. They tend to see humans as the centre and measure of everything. The consequence of this is the alienation of God from the universe, the need for religion and the mainstreaming of humans over everything. If examined more deeply, the problem of humanism enters the area of worldview, namely how we see reality and truth. Therefore, with a critical analysis and supported by literature study, the researcher seeks to dissect the problem of humanism and compare it with how Islam conceptualises the problem.